PENERAPAN METODE BIL QOLAM DALAM PEMBELAJARAN AL QUR’AN DI SMAI AL MAARIF SINGOSARI MALANG - Moch Dzulfikar Arif; Anwar Sa’dullah; Adi sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This study aims to describe 1) the application of the bil qolam method in learning the Qur'an at SMAI Al Maarif Singosari Malang, 2) knowing the ability to read the Qur'an of students at SMAI Al Maarif Singosari, 3) knowing the obstacles experienced in learning the Qur'an. at SMAI Al Maarif Singosari. In this study, the research method used was descriptive qualitative research, taking the background of SMAI Al Maarif Singosari. The Bil Qolam method in teaching the Qur'an is a learning concept that uses the talqin-taqlid technique (imitating) and is characterized by 4 PIQ songs. The song is easy to apply in reading the Qur'an and produces good reading. Al-Qur'an learning at SMAI Al Maarif Singosari is not much different from the application of the Bil Qolam method in the guidebook.